Perkembangan Pendidikan Indonesia pada Zaman Penjajahan Ii (Abad 20 Termasuk Masa Pendudukan Jepang) - Fuadi, Danna Aditya Rahma; Al Anshori, Devgano Risydan (Global Education Journal, 2023)
The colonization that occurred in Indonesia during the 20th century, both by European countries and Japan, brought significant changes in the development of education in Indonesia. Prior to the Japanese occupation, the education system in Indonesia was dominated by the Dutch education system which was elitist and limited. This study aims to examine the development of Indonesian education during the period of the second colonization, especially during the Japanese occupation. Through a historical approach and document analysis, this study discusses important changes in the education system that occurred during that period. This study also discusses the positive and negative impacts of these changes. The results of the study show that during the Japanese occupation, education in Indonesia underwent significant development, such as the opening of educational opportunities for all without exception and the introduction of new ideas in the education system, such as vocational education. However, the development of education in Indonesia during that time also had a negative side, such as education being directed to support Japan's interests and discriminating against local languages. This study provides an important contribution to understanding the history of education development in Indonesia, especially during the period of the second colonization. The results of this study can also provide guidance for future education development.